Music Training as a Therapeutic Medium for Students with Autism at Sforzando Music School - Liadi, Gregory (Universitas Negeri Surabaya, 2026)
This study explores the effectiveness of music training as a therapeutic medium for students with autism at the Sforzando Music School, using a descriptive qualitative approach. Data were collected through passive participant observation, structured interviews with the school founder, teachers, and parents, and document analysis. The analysis shows Sforzando's structured program, which covers nine aspects of development (Salim, 2006) and five main benefits of music as therapy (Salim, 2009), significantly supports the holistic development of autistic children. Case studies of five students demonstrate substantial progress in communication, self-regulation, and social interaction. This study concludes that music training at Sforzando is not merely an additional activity but a powerful therapeutic tool for the comprehensive development of autistic students.